Bacteriological profile and antimicrobial susceptibility pattern of urinary tract infection in pregnant women during routine antenatal visit in a tribal district of West Bengal, India - Sayantani Endow; Rahul Sikdar; Amiya Kumar Pandit; Hiranmoyee Mahata (Asian Journal of Medical Sciences)
Background: Urinary tract infection (UTI) is a relatively serious infection in pregnant women as it puts the health of both mother and fetus at risk. UTI encompasses a wide spectrum ranging from asymptomatic bacteriuria to symptomatic cystitis to the most dreaded complication, pyelonephritis. As the frequency of UTI in pregnancy is much more as compared to non-pregnant women, early diagnosis and treatment are very essential for the well-being of both mother and fetus.